1965
DOI: 10.1111/imj.1965.14.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary Disorder in Parkinsonism

Abstract: Summary The alimentary symptoms found in 107 consecutive cases of Parkinsonism have been compared with those found in 96 control subjects. Chewing difficulty, drooling of saliva, dysphagia, frequent heartburn and constipation all occurred significantly more often in Parkinsonism than in controls, and of these symptoms only the incidences of dysphagia and heartburn did not correlate with increasing disability from Parkinsonism. There was relatively little correlation between alimentary symptoms and ætiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0
16

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 36 publications
6
82
0
16
Order By: Relevance
“…Therefore in future studies of disturbances in the auto nomic regulation in Parkinson's syndrome only patients with IPD should be examined; thus, in the examinations the pathogenesis of Parkinson's syndrome should be tak en into consideration. Vegetative disturbancees in the upper gastrointestinal tract are very common [19,20]. Whether these should also be divided into separate groups according to the etiology of the Parkinson syndrome has to be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in future studies of disturbances in the auto nomic regulation in Parkinson's syndrome only patients with IPD should be examined; thus, in the examinations the pathogenesis of Parkinson's syndrome should be tak en into consideration. Vegetative disturbancees in the upper gastrointestinal tract are very common [19,20]. Whether these should also be divided into separate groups according to the etiology of the Parkinson syndrome has to be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Since James PARKINSON's original description of Parkinson's disease (PARKINSON, 1817), the occurrence of alimentary symptoms such as dysphagia, heartburn and constipation has been well documented for the disease (EADIE and TYRER, 1965;AMINOFF and WILCOx, 1971). Radiologically, diminished peristalsis and dilatation of the esophagus, megacolon, and dilatation of the small intestine have also been reported (LEWITAN et al, 1951;GIBBERD et al, 1974;LOGE-MANN et al, 1975).…”
Section: Significance Of Lewy Bodies In the En-teric Nervous System Imentioning
confidence: 99%
“…Postmortem studies of patients with Parkinson's disease have shown that the loss and degeneration of pigmented neurons and occurrence of concentric hyaline cytoplasmic inclusions-the Lewy bodies-in the substantia nigra and locus ceruleus are constant pathological findings in the disease (GREENFIELD and BOSANQUET, 1953;BETHLEM and DEN HARTOG JAGER, 1960). However, there have been few morphological studies on the nervous system of the alimentary tract in Parkinson's disease, although autonomic symptoms in the alimentary tract have been well documented as constant clinical features of the disease (EADIE and TYRER, 1965;AMINOFF and WILCOx, 1971).…”
mentioning
confidence: 99%
“…Swallowing disorders in Parkinson's disease have been reported by several investigators [1,2,7,19,20,27,29). Lieberman and co-workers {19] found that dysphagia, as assessed by barium swallow, may be present in as many as 50% of patients with the disease.…”
mentioning
confidence: 97%